Barriers faced by the Brazilian business community to access the United States market system - Anzanello, Adrienne Cardoso (2007)
Trade history between Brazil and the United States is long and complicated but it is only in recent years that the trade balance has become more equal in terms of both imports and exports. As Brazil continues to establish its position in the world economy and expand its export market it is only natural that it seeks to increase exports to its single largest trading partner, the United States, and maintain the market share already established. In order to achieve success in these regards Brazil must have a deep understanding of the American political economy system. Part of this entails understanding barriers that must be overcome by Brazilian businesses to access United States markets, particularly the access of certain products at the industry level.